THE EFFECTIVENESS OF PUBLIC SERVICES AT THE PANGI VILLAGE OFFICE SUWAWA TIMUR SUB-DISTRICT - Bulonggodu, Yurni; Isa, Rusli; Tohopi, Rustam (Universitas Negeri Gorontalo, 2024)
The research objectives were to find out (1) How is the Effectiveness of Public Services at the Pangi Village Office, East Suwawa District. (2) Factors that Determine the Effectiveness of Public Services at the Pangi Village Office, East Suwawa District. This research method uses a qualitative approach with a qualitative description type of research. Based on the results of the research found in the field that (1) The effectiveness of public services at the Pangi Village Office, East Suwawa District, researchers use three indicators of the effectiveness of an organization's work at the Pangi Village Office, namely the time factor, the accuracy factor, the service provider style factor. The time factor or timeliness in service providers, is still not optimal, marked by the fact that there are still officials who have not been able to complete their work on time. The accuracy factor in the service provider is good and has been effectively characterized by high accuracy and accuracy in every service. The service provider style factor is effective, characterized by being by existing service procedures and following the specified mechanism. (2) Factors that determine the effectiveness of public services at the Pangi Village Office, East Suwawa District include ability, expertise, knowledge, attitude, motivation, and stress have been carried out well and can be said to be effective.